Construction Method Optimization for Transfer Section Between Cross Passage and Main Tunnel of Metro Station - Zhou, P. Y.; Wang, J. B.; Song, Z. P.; Cao, Z. L.; Pei, Z. M. (Frontiers in Earth Science, 2022)
The transfer section between the cross passage and the main tunnel is the part that needs to be paid attention to during the underground excavation construction of the subway. Due to the complex stress, the collapse of the horsehead gate and excessive surface settlement often occur. In order to determine the construction scheme of the transfer section between the cross passage and the main tunnel of Guanshui Road Station of Metro Line 2 in Guiyang, China, the numerical simulation method was used to analyze the “double-holes interval pillar method”, “sector expansion method” and “gate climbing method” respectively. The mechanical response of surrounding rock and supporting structure with each method was compared. The comparison showed that the surface settlement, the displacement of the cave and the plastic zone caused by the double-holes interval pillar method were the smallest, and the method can reduce the construction risk, shorten the construction period and reduce the project cost. Therefore, it was recommended to use the double-holes interval pillar method to construct the transfer section. The comparison between the measured deformation data and the numerical simulation results of the double-holes interval pillar method showed that the numerical simulation results were smaller than the measured deformation at each point, and the surface settlement and horizontal displacement in the tunnel both meet the safety control standard.